2018
DOI: 10.3130/aija.83.1687
|View full text |Cite
|
Sign up to set email alerts
|

Surface Geometry and Architectural Design Activities

Abstract: For the ecological understanding of architectural design activities Hiroki SEKI This paper shows the possibilities of understanding architectural design activities from the perspectives of James J. Gibson's ecological approach to human behavior. Architectural design activities have not been considered from the viewpoint of Gibson's approach, although other architectural studies, such as studies of environmental behavior, have been applying his approach. First, this paper examines Gibson's unpublished memorandu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The important characteristics of an image signal are generally contained in its phase spectrum, not in its amplitude spectrum. 26 In view of the role of the discrete fractional transform domain phase spectrum information in the feature extraction of two-dimensional digital images, the following analysis is carried out: E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 1 3 ; 1 1 6 ; 1 8 9 Q l ðw; uÞ ¼ LL a b l ðPðx; yÞÞ;…”
Section: Image Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important characteristics of an image signal are generally contained in its phase spectrum, not in its amplitude spectrum. 26 In view of the role of the discrete fractional transform domain phase spectrum information in the feature extraction of two-dimensional digital images, the following analysis is carried out: E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 1 3 ; 1 1 6 ; 1 8 9 Q l ðw; uÞ ¼ LL a b l ðPðx; yÞÞ;…”
Section: Image Feature Extractionmentioning
confidence: 99%
“…The research found that in the FFT of an image, the phase spectrum and the amplitude spectrum often play different roles. The important characteristics of an image signal are generally contained in its phase spectrum, not in its amplitude spectrum 26 . In view of the role of the discrete fractional transform domain phase spectrum information in the feature extraction of two-dimensional digital images, the following analysis is carried out: Ql(w,u)=LLla¯b¯(P(x,y)),Qll(w,u)=Llla¯b¯(P(x,y)).…”
Section: Smart Image Technologymentioning
confidence: 99%